Keterampilan Lompat Jauh Siswa Sekolah Dasar - Moch. Asmawi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: The present study aims at evaluating the relationship between flexibility and power and long jump performance. The present study is a descriptive survey. A sample of 40 male elementary school students of Sekolah Dasar Negeri 03 Pagi Pondok Bambu, Jakarta Timur was drawn using a random sampling technique. The study revealed that flexibility accounted for 8,82%, power 35,7%.The present study concluded that there is a positive relationship between flexibility and power and the students’ long jump performance. The greater flexibility is and the greater power is, the farther the jump will be.